(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
This thesis explores the physical and chemical properties of semiconducting polymers, their structural features, operational principles, and production technologies. The significance of organic semiconducting polymers—such as polyaniline, polypyrrole, and polythiophene—in modern nanoelectronics, optoelectronics, and energy devices is analyzed. The synthesis processes, doping techniques, and application methods (such as spin-coating and inkjet printing) are discussed in detail. Practical applications in devices like organic light-emitting diodes (OLEDs), organic photovoltaics (OPVs), and biosensors are also presented. As a result, the technological potential and future prospects of semiconducting polymers are summarized and evaluated.